Pengembangan Website E-Labmaintenance Dalam Pemeliharaan Alat Aboratorium Pendidikan Keperawatan - Haryanti, Rizki Sri; Dona, Mery; Novianti, Lily (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2024)
Background: Laboratory equipment requires good maintenance in order for the equipment to be used in the long term. The application of good maintenance is by carrying out technical matters and carrying out administrative activities in an orderly manner. The nursing laboratory at the research site still makes equipment maintenance scheduling manually. Maintenance has also not been carried out and documented properly. Objective: This study aims to produce a website-based information system (E-Labmaintainance) in the maintenance activities of nursing education laboratory equipment at the Poltekkes Kemenkes Palembang. Methods: The method used in this research is Research and Development (RND) through modification of 6 (six) research steps, namely identification and potential problems, product design, stage I design validation, design revision, stage II design validation and trial use. Validation was carried out by 2 (two) experts in technology and informatics. The trial of use was carried out by 5 (five) Educational Laboratory Staff on duty spread across 4 (four) nursing education laboratories, namely the Palembang Nursing Laboratory, Lubuk Linggau Nursing Laboratory, Baturaja Nursing Laboratory and Lahat Nursing Laboratory. The validity assessment uses the Aiken Item Validity Index formula. Results: The results of the research are in the form of e-labmaintenance web pages that have been validated and tested to penggunas. The final validation results from the expert obtained a validity value of “very high” with a value of V = 0.94. This is decomposed from the validity value of the application usability is very high (0.94), the validity of the ease of use of the application is very high (0.92), the validity of the ease of learning is very high (1.00) and the validity of pengguna satisfaction is also very high (0.85). The results of the trial to the pengguna also obtained the results of 'very high” validity with a value of V = 0.82. Conclusion: E-labmaintenance website is feasible to use in equipment maintenance activities in the nursing education laboratory of the Palembang Poltekkes Kemenkes.